How To Be A Real Person (In Just One Day) - Warner, Sally (New York Alfred A. Knopf, 2001)
Sixth grader Kara tries to conceal from her friends, her absent father, and the authorities that her mother is sliding deeper and deeper into mental illness.
Keywords: Mental illness; Mothers and daughters